Successful single‐session endosonography‐based endoscopic retrograde cholangiopancreatography without fluoroscopy in pregnant patients with suspected choledocholithiasis: a case series. Issue 2 (20th June 2013) - Vohra, Sheba; Holt, Edward W.; Bhat, Yasser M.; Kane, Steve; Shah, Janak N.; Binmoeller, Kenneth F.
Abstract Purpose Same session endosonography (EUS) immediately prior to scheduled endoscopic retrograde cholangiopancreatography (ERCP) may eliminate the need for ERCP and its associated risks in pregnant patients with no evidence of choledocholithiasis on EUS. In patients with choledocholithiasis, EUS provides information regarding the location, size and number of stones present, which helps guide biliary interventions and confirm stone clearance without the use of fluoroscopy. Methods We retrospectively identified 10 pregnant patients referred to our tertiary endoscopy center for suspected choledocholithiasis between June 2008 and January 2012. All patients underwent same‐session EUS‐based ERCP. Results Of 10 pregnant patients managed with EUS‐guided ERCP, six were found to have common bile duct stones and went on to ERCP. Four patients with no evidence of choledocholithiasis on EUS did not undergo ERCP. Patients with confirmed choledocholithiasis underwent ERCP without the use of fluoroscopy using the additional information provided by EUS. Conclusions Same‐session EUS immediately prior to scheduled ERCP may eliminate the need for ERCP and its risks in pregnant patients with no evidence of choledocholithiasis on EUS. In patients with confirmed choledocholithiasis, EUS provided additional information regarding the location, number and size of bile duct stones, which enabled the successful clearance of the bile duct without the use of fluoroscopy.